Which MBA? : a critical guide to the world's best MBAs - Bickerstaffe, George (Pearson Education ; Economist Intelligence Unit, 2000)
"Revised and restructured, the twelfth edition of Which MBA? offers a fully comprehensive and authoritative guide of MBAs worldwide. Based on extensive research by the Economist Intelligence Unit, including on-campus visits, advice and quotes from current students or recently graduated alumni, this book presents an unbiased, detailed assessment of all the key issues to consider before embarking on an MBA."--BOOK JACKET.